2016
DOI: 10.1016/j.bjan.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo entre cloridrato de benzidamina em gel, lidocaína a 5% em gel e lidocaína a 10% em spray no balonete do tubo endotraqueal em relação à dor de garganta pós‐operatória

Abstract: Postoperative sore throat is a common complication after endotracheal intubation. After tracheal intubation, the incidence of sore throat varies from 14.4% to 50%. The aim of the study was to compare between benzydamine hydrochloride gel, lidocaine 5% gel and lidocaine 10% spray on the endotracheal tube cuff as regards postoperative sore throat. The present study was carried out on 124 patients admitted to Alexandria university hospitals for lumbar fixation surgery requiring general anesthesia. Patients were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Finally, we included 13 RCTs for this systematic review and meta-analysis (Fig. 1, Table 1) [7][8][9][21][22][23][24][25][26][27][28][29][30]. The inter-rater agreement between the four systematic reviewers, using the kappa statistic, was κ = 0.62.…”
Section: Search Resultsmentioning
confidence: 99%
“…Finally, we included 13 RCTs for this systematic review and meta-analysis (Fig. 1, Table 1) [7][8][9][21][22][23][24][25][26][27][28][29][30]. The inter-rater agreement between the four systematic reviewers, using the kappa statistic, was κ = 0.62.…”
Section: Search Resultsmentioning
confidence: 99%
“…In a comparative study, it was established that the benzydamine hydrochloride gel on the ETT cuff is a simple and effective method that can significantly decrease the severity of postoperative sore throat compared with 10% lidocaine, 5% lidocaine, and normal saline 49 . However, in a subsequent study done by Yhim et al, it was concluded that application of prophylactic benzydamine hydrochloride spray to the vocal cords and upper trachea did not show a reduction in postoperative sore throat in the pediatric population 50 .…”
Section: Medications and Anti‐inflammatory Response Therapiesmentioning
confidence: 99%
“…Corticosteroids Both IV and topical ETT coatings have shown to reduce airway edema and inflammation and reduce the incidence of postextubation airway stridor and sore throat. [42][43][44][45][46][47] Benzydamine hydrochloride gel Has shown variable results, with benzydamine hydrochloride gel ETT coating shown to be effective in decreasing postoperative sore throat severity, 49 but showing no reduction when applied as a spray. 50 Possible future therapies Ketamine Ketamine gargles demonstrated a significant decrease in postoperative sore throat.…”
Section: Drug/coatingmentioning
confidence: 99%